From Likes to Learning: Innovative Strategies for Using Social Media to Boost Gen Z Academic Performance - Titi Prihatin; Ghanis Putra Widhanarto; Ali Formen; Seftia Kusumawardani (Journal of Pedagogy and Education Science, 2026)
The existing literature acknowledges the potential of social media to enhance online learning, but a significant gap exists in comprehensively understanding how teachers' specific social media skills directly influence the quality of online learning experiences and student outcomes. This research examines how teachers' social media skills relate to their perceptions of online learning quality, focusing on both the predictive influence of these skills and their correlation with teachers' evaluations of online learning. This quantitative study, utilizing surveys and statistical analyses such as descriptive statistics, Pearson correlation, and simple linear regression, investigates the relationship between teachers' social media skills (independent variable) and the quality of online learning (dependent variable), confirming the validity and reliability of the instruments used through content and construct validity assessments and Cronbach's alpha values. The result finds that teachers' social media skills have a positive impact on the quality of online learning, as well as student engagement and interaction. Educational institutions can support teachers in enhancing their online teaching by providing training on the effective use of social media tools and platforms. This study implies that investing in teachers' social media skills training can significantly enhance the quality of online learning experiences and student engagement in the digital age.